THE IMPACT OF ONLINE REVIEWS QUALITY ON TOURISM INTENTION IN THE CONTEXT OF RED BOOK: THE MEDIATING ROLE OF DESTINATION IMAGE IN MACAO - Liu, Cui Feng (2025)
This study focuses on the influence of online review quality on tourism intention, with destination image as a mediating variable, in the context of the rapid rise of internet content platforms like Red Book and Douyin. The platforms like Red Book and Douyin play an important role in shaping travel behavior, as potential travelers frequently rely on user-generated content (UGC) to find information about travel destinations, plan their trips, and form perceptions of destinations. Through a comprehensive review of existing literature and the application of structural equation modeling (SEM), the study reveals that the cognitive and affective image of destination are significantly influenced by the quality of online reviews, which in turn impacts overall destination image and tourism intention. The findings demonstrate that higher-quality online reviews — those that are timely, sufficient，helpful, and credible — not only enhance the cognitive understanding of destinations but also evoke stronger emotional connections, ultimately fostering a higher likelihood of travel intention. Moreover, the study highlights the mediating role of destination image during the process where online review quality influences tourism intention. These results offer critical insights for destination marketing organizations (DMOs) in conducting tourism marketing to attract tourists by strategically enhancing the quality and authenticity of online reviews. The study also identifies limitations in sample selection and mediating variables, providing directions for future research in the fields of online content, destination image, and tourism behavior.